INFLUENCE OF ORGANIZATION CAPABILITIES ON WATER SERVICE DELIVERY IN WAJIR COUNTY, KENYA - Abdille, Osman Kurash; Nzulwa, Robert (European Journal of Business and Strategic Management, 2016)
Purpose: The main objective of the study was to establish the influence of organization capabilities on water service delivery in Wajir County, Kenya. Methodology: The study adopted a descriptive research design. Findings: Results revealed that the level of financial capabilities, innovation capabilities, human resource management capabilities and leadership capabilities of the water service providers was poor. Correlation results also revealed that financial capabilities, human resource management capabilities and leadership capabilities were positively and significantly associated with water service delivery. Regression results also revealed that financial capabilities, human resource management capabilities and leadership capabilities had a positive and significant relationship with water service delivery. Unique contribution to theory, practice and policy: The Water Services Boards (WSBs) will benefit from this study by obtaining details on how organization capabilities impact on water service delivery. This will help them to help find lasting solutions to numerous external and internal challenges which hinder effective water service delivery. The Ministry of Water and Irrigation may better understand how organization capabilities influence water service delivery. In this respect the policy makers can come up with new policies which require the employees in the Water Service Boards (WSBs) be trained so as be acquitted with the relevant organization capabilities such as financial capabilities, human resource management capabilities and leadership capabilities so as to ensure sustainable water service delivery to the public. This study is also intended to add knowledge to previous studies done on organization capabilities by primarily focusing on organization capabilities in water service delivery.